2017
DOI: 10.1016/j.aquaculture.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination or monochloramination: Balancing the regulated trihalomethane formation and microbial inactivation in marine aquaculture waters

Abstract: Disinfection methods like chlorination are increasingly used to sanitize the water, equipment, tools and surfaces in aquaculture facilities. This is to improve water quality, and to maintain a hygienic environment for the well-being of aquatic organisms. However, chlorination can result in formation of regulated disinfection byproducts (DBPs) that can be carcinogenic and toxic. This study aims to evaluate if an optimal balance can be achieved between minimal regulated DBP formation and effective microbial inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our results also have broad implications for engineered, agricultural, food and natural systems, where chloramine exists. For example, chloramines are commonly used as disinfectants in households, commercial cleaning, and food and health industries. Similarly, the widespread practice of chlorine-based disinfection of nitrogen-rich recreational water pools and agricultural waste streams (e.g., lagoons storing animal manure, animal waste, aquaculture effluent), can lead to potential formation of chloramines in these waste streams. Furthermore, UV-based treatments of produced water, brackish groundwater, and desalination concentrate generate chloramine in the system. , The methodologies developed for trace organic contaminant degradation in this study are applicable to these chloramine- and halogen-impacted environmental- and engineered-systems.…”
Section: Resultsmentioning
confidence: 99%
“…Our results also have broad implications for engineered, agricultural, food and natural systems, where chloramine exists. For example, chloramines are commonly used as disinfectants in households, commercial cleaning, and food and health industries. Similarly, the widespread practice of chlorine-based disinfection of nitrogen-rich recreational water pools and agricultural waste streams (e.g., lagoons storing animal manure, animal waste, aquaculture effluent), can lead to potential formation of chloramines in these waste streams. Furthermore, UV-based treatments of produced water, brackish groundwater, and desalination concentrate generate chloramine in the system. , The methodologies developed for trace organic contaminant degradation in this study are applicable to these chloramine- and halogen-impacted environmental- and engineered-systems.…”
Section: Resultsmentioning
confidence: 99%
“… 9 Residual antibiotics are degraded during the chlorination process; however, studies have found that antibiotics undergo side reactions with chlorine disinfectants to generate halogenated disinfection by-products (H-DBPs) such as trihalomethanes (THMs) and haloacetic acids (HAAs). 10,11 These H-DBPs have attracted extensive attention in the field of scientific research owing to the latent health risks. 12 In seawater, hypobromous acid (HOBr) can be generated by the chlorine oxidation to be dominant oxidant species, leading to preferential formation of various brominated by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Physical cleaning is generally more effective for the reversible foulant layer (10), while chemical cleaning is used to remove irreversible foulant layers (11). However, the use of these chemicals can lead to the formation of carcinogenic and toxic byproducts, and can detrimentally impact the membrane integrity (12,13). In addition, it was shown that certain bacteria, such as Acinetobacter spp.…”
Section: Introductionmentioning
confidence: 99%